Clairaut's Theorem
The equation of the clairaut's form is as given: y = xy′+ ψ(y′), where ψ(y′) = a nonlinear differentiable function. The Clairauts equation is a special case of the Lagrange equation when φ(y′) equals y′. It is solved in the same manner by establishing a parameter. A standard solution is assigned as y = Cx + ψ(C), where C = an arbitrary constant.
Likewise, the Lagrange equation, the Clairaut equation also may contain a singular solution which is expressed parametrically in the form:
x = −ψ′(p)
y = xp + ψ(p)
,where p = parameter.
Clairaut Differential Equation
Clairaut form of the differential equation is basically a 1st -order differential equation of the form: y = x dy/dx + f (dy/dx)
In which, f is a suitable function.
Differential Equation Solution Method and Formula
Differentiate both sides in terms of x and obtain:
dy/dx = dy/dx + (x + f' (dy/dx)) d²y/d²x
Cancel the common term from both the sides of equation and get:
0 = (x + f' (dy/dx)) d²y/d²x
This provides two possible solution types as below:
D²y/d²x = 0
x + f'(dy/dx) = 0
Remember that when we differentiate, we lose details, so it is not true that all solutions of the differentiated equation solve the actual equation. Instead, we require plugging these solutions into the actual equation to compel them. We get the following:
The solutions for the d²y/d²x = 0 case are straight lines in the form y = Cx + f(C). This is the solution family for the general solution of the differentiated equation.
The solution for the x + f'(dy/dx) = 0 case is special: it is a parametric curve provided by x = -f'(p), y = f(p) - pf'(p) in which p = dy/dx is the parameter moving along the curve. This is referred to as the singular solution. The curve resembling this is the envelope of the general solution curves. For the purpose of verifying that this solution is right, we can compute dy/dx with the help of parametric differentiation with reference to p and check that it is indeed equivalent to p.
Solved Example
Example:
1. Evaluate the general and singular solutions of the clairaut differential equation form y = 2xy' – 3 (y') 2.
Solution:
Here we observe that we manage a Lagrange equation. We will solve it with the help of the method of differentiation.
Represent y′= p, so the equation is expressed in the form:
y
Differentiating both sides of the equation, we find:
dy = 2xdp + 2pdx − 6pdp.
Now, you can replace dy with pdx:
pdx = 2xdp + 2pdx − 6pdp, ⇒ −pdx = 2xdp − 6pdp.
Dividing by p, we can express the following mathematical equation (further we check if p = 0 is a solution of the original equation):
−dx = 2xpdp − 6dp, ⇒ dxdp + 2px – 6 = 0.
As it can be observed, we get a linear equation for the function x (p). The integrating factor is \[u(p) = exp (\int \frac{2p}{dp}) = exp(2ln\left| p\right|) = exp(ln\left| p\right|2) = |p^{2} = p^{2}\].
The general solution of the linear equation of the form is assigned as:
\[X(p) = \int p^{2}.6dp + \frac{C}{p^{2}} = \frac{6p^{3}}{3} + \frac{C}{p^{2}} = 2p + \frac{C}{p^{2}}\].
By substituting this expression for x into the Lagrange equation, we get:
y = 2(2p + Cp²)p − 3p² = 4p² + 2Cp − 3p² = p² + 2Cp.
Therefore, the general solution in parametric form is explained by the methodology of equations:
{X (p) = 2p + C/p²
{X (p) = p² + 2C/p
Apart from that, the Lagrange equation can contain a singular solution. Solving the equation φ (p) − p = 0, we determine the root:
2p − p = 0, ⇒p = 0.
Thus, the singular solution is written by the linear function:
y=φ (0)x + ψ(0) = 0⋅x + 0 = 0.
FAQs on Clairaut's Equation
1. How to find the solution of v=u dv/du +(dv/dvu)² , where u=y and v=xy?
Suppose that, dv/du = q.
Then the provided differential equation obtains the form:
v = uq + q²
Thus, the general solution is
v = uc + c²
Or, xy = cy + c² (considering the values of u and v)....... (1)
Now the singular solution of the differential form of equation be the envelope of the family of straight lines denoted by equation (1) and it is provided by the equation
y² + 4xy = 0
(discriminant of (1)) = 0 will be the envelope.
Or, y(y+4x) = 0.
y = 0 or y = −4x denotes the singular solution of the provided differential equation.
So options (A), (B) and (C) are correct.
2.What is meant by the Lagrange Equation?
A clairaut differential equation is of the form; y = xφ(y′) + ψ(y′), where φ(y′) and ψ(y′) are said to be the functions differentiable on a fixed interval, is known as the Lagrange equation.
By establishing y′= p and differentiating in terms of x, we obtain the general solution of the equation in parametric form:
given that φ(p) − p ≠ 0, where p represents a parameter.
The Lagrange equation may also contain a singular solution if the condition φ(p)−p ≠ 0 is failed. The singular solution is provided by the expression: y = φ(c)x + ψ(c), where represents the root of the equation φ =